Does Neutrophil Phenotype Predict the Survival of Trauma Patients? - Mortaz, Esmaeil; Zadian, Seyed Sajjad; Shahir, Mehri; Folkerts, Gert; Garssen, Johan; Mumby, Sharon; Adcock, Ian M. (Frontiers in Immunology, 2019)
According to the World Health Organization (WHO), trauma is responsible for 10% of deaths and 16% of disabilities worldwide. This is considerably higher than those for malaria, tuberculosis, and HIV/AIDS combined. While the human suffering and death caused by injury is well-recognized, injury has a significant medical care cost. Better prediction of the state of trauma patients in the days immediately after trauma may reduce costs. Traumatic injuries to multiple organs can cause dysfunction in all systems of the body especially the immune system placing patients at high risk of infections and inflammatory complications which are often fatal. Neutrophils are the most abundant leukocyte in the human circulation and are crucial for the prevention of microbial disease. Significant changes in neutrophil functions such as enhanced chemotaxis, Neutrophil extracellular trap (NET)-induced cell death (NETosis), and phagocytosis occur early after injury followed by prolonged functional defects such as phagocytosis, killing mechanisms, and receptor expression. Analysis of these changes may improve the prediction of the patient's condition over time. We provide a comprehensive and up-to-date review of the literature investigating the effect of trauma on neutrophil phenotype with an underlying goal of using this knowledge to examine the predictive potential of neutrophil alterations on secondary complications in patients with traumatic injuries. We conclude that alterations in neutrophil surface markers and functions may be potential biomarkers that predict the outcome of trauma patients.